The Quality of Life for Family Caregivers in Caring Family Members Undergoing Hemodialysis - Uswatun Hasanah; Sapti Ayubbana; Supardi Supardi (Proceedings of the International Conference on Nursing and Health Sciences, 2020)
Family caregivers who care for family members undergoing hemodialysis are affected quite difficult. The impact on family caregivers in caring for patients undergoing hemodialysis is emotional, social, physical, and financial so that it has an impact on their quality of life. The aims of this study is to describe the quality of life of the family caregiver in patients undergoing hemodialysis. This research is a quantitative study with an analytic descriptive approach. The research sample consisted of 56 family caregivers. The sampling technique used purposive sampling. Measurement of quality of life data for family caregivers using the WHOQOL-BREF quality of life instrument. Data were analyzed univariately with a frequency distribution. The results showed that the majority of family caregivers experienced a low quality of life with an average value below 50. The lowest average results were in the domain of social relationships (mean: 32.928), followed by psychological domains, environmental domains and physical health.